2022
DOI: 10.20944/preprints202202.0320.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alteration in Long Noncoding RNAs in Response to Oxidative Stress and Ladostigil in SH-SY5Y Cells

Abstract: Microglia activation causes neuroinflammation, which is a hallmark of neurodegenerative disorders, brain injury, and aging. Ladostigil, a bifunctional reagent with antioxidant and anti-inflammatory properties, reduced microglial activation and enhanced brain functioning in elderly rats. In this study, we studied SH-SY5Y, a human neuroblastoma cell line, and tested viability in the presence of hydrogen peroxide and Sin1 (3-morpholinosydnonimine), which generates reactive oxygen and nitrogen species (ROS/RNS). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
(94 reference statements)
0
0
0
Order By: Relevance
“…We observed that the antiviral effect was amplified by KD of DJ-1 (with ~200 overexpressed genes and ~100 non-coding RNAs). While no function is known for most of these non-coding RNAs, the upregulation of lncRNA of NEAT1 (2.2 folds, q-value 3.7e-05) is intriguing, as NEAT1 was proposed to be upregulated in response to oxidative stress [48] and as a potential biomarker in Parkinson's diseases [49]. We questioned whether the effect of KD of DJ-1 is through signaling convergence of the IFN signaling pathways or, alternatively, through the failure of the cells to cope with the alteration in the change in redox level.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the antiviral effect was amplified by KD of DJ-1 (with ~200 overexpressed genes and ~100 non-coding RNAs). While no function is known for most of these non-coding RNAs, the upregulation of lncRNA of NEAT1 (2.2 folds, q-value 3.7e-05) is intriguing, as NEAT1 was proposed to be upregulated in response to oxidative stress [48] and as a potential biomarker in Parkinson's diseases [49]. We questioned whether the effect of KD of DJ-1 is through signaling convergence of the IFN signaling pathways or, alternatively, through the failure of the cells to cope with the alteration in the change in redox level.…”
Section: Discussionmentioning
confidence: 99%